Unusual presentation of eosinophilic fasciitis (EF) with a raised ALT. Issue 1 (22nd December 2018) - Batty, Thomas; Majeed, Shuja; Wlodek, Christina; Gunawardena, Harsha
Abstract : Eosinophilic fasciitis (EF) is a syndrome of unknown aetiology characterised by progressive collagenous thickening of the subcutaneous fascia. Limb oedema can precede the skin thickening and induration classically associated with EF. We describe a case of EF in a 31-year-old woman who presented to her general practitioner with lower limb oedema and stiffness. Blood tests in primary care showed a persistently raised alanine transferase (ALT). No hepatic cause for her raised ALT was found despite investigation. The unusual manner of her presentation led to delay in her referral to the autoimmune connective tissue disease (CTD) clinic. This case illustrates the importance of considering autoimmune CTD such as EF in young patients presenting with limb oedema and raised ALT, as early treatment influences prognosis and functional recovery.